2016
DOI: 10.5897/ajest2015.2014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biochar on soil properties and lead (Pb) availability in a military camp in South West Ethiopia

Abstract: Application of biochar to soil can improve numerous physicochemical and biological properties of the soil. The method for lead metal (Pb) remediation in soil is a challenge worldwide. The excessive Pb accumulation in the soil can radically reduce the soil quality and fertility. This study was conducted to find out the efficiency of biochar in improving the physicochemical properties of soil and to evaluate its effect on Pb availability in a military camp soil. Soil sample was collected from military camp of Ji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 37 publications
2
15
1
Order By: Relevance
“…Relationships between soil fertility, plant nutritional status, and grain yield Significant positive correlations recorded between the mineral-N, available P, and available K contents in soil and P and N concentration in aboveground biomass of wheat suggested that biochar and RHA supplied significant amounts of these nutrients to plants (Figure 1). Higher bioavailability and release of biochar's N, P, and K in soil have been reported in a number of earlier studies (Bayu et al, 2016;Mete et al, 2015;Yu et al, 2009). Among the soil fertility parameters, SOC content showed significant correlation with wheat grain yield (Figure 2).…”
Section: Crop Yield and N Use Efficiency As Affected By Biocharsupporting
confidence: 56%
“…Relationships between soil fertility, plant nutritional status, and grain yield Significant positive correlations recorded between the mineral-N, available P, and available K contents in soil and P and N concentration in aboveground biomass of wheat suggested that biochar and RHA supplied significant amounts of these nutrients to plants (Figure 1). Higher bioavailability and release of biochar's N, P, and K in soil have been reported in a number of earlier studies (Bayu et al, 2016;Mete et al, 2015;Yu et al, 2009). Among the soil fertility parameters, SOC content showed significant correlation with wheat grain yield (Figure 2).…”
Section: Crop Yield and N Use Efficiency As Affected By Biocharsupporting
confidence: 56%
“…Soil pH influences the availability of plant nutrients. The decrease in soil pH following the application of biochars and poultry manure contradicts the findings of [13][14][15] all of whom recorded increased pH after the application of biochar and compost. It is however worth to note that the impact of biochar/manure application on soil pH would be much influenced by the properties of the feedstock from which they are prepared.…”
Section: Soil Ph and Electrical Conductivitymentioning
confidence: 57%
“…In an Iowa study, [17] found a significant increase in Ca 2+ levels when biochar was applied to soil at 20 g Kg -1 soil. [13][14][15] also observed significantly increase in the levels of Ca +2 , Mg 2+ , K + and Na + following the application of biochar and compost. Per these research findings, therefore, biochar could be a significant source of these cations [4] and could potentially help in sodic soil remediation.…”
Section: Exchangeable Ca 2+ Mg 2+ K + and Na +mentioning
confidence: 99%
“…The presence of K in the feedstock alters C degradation due to a greater thermal stability of organic compounds formed during pyrolysis [54]. In another study, the addition of 15 t ha −1 coffee husk biochar (pyrolyzed at 500 • C) in an acid soil also increased the CEC from 24.9 to 34.9 cmol c kg −1 after three months of incubation as a result of the high CEC of the biochar (79 cmol c kg −1 ) [37]. For both clayey and medium texture soils used in this study, the CEC values are the highest already reported for Brazilian weathered soils.…”
Section: Soil Cation Exchange Capacitymentioning
confidence: 95%
“…Although several studies report positive contribution of biochar to soil CEC [37][38][39], the mechanism behind soil CEC increase in short and medium-term experiments is not clear [40,41]. In that direction, the evaluation of CEC of soils amended with biochar should be supported by other studies based on the use of tailored biochars from feedstocks exposed to variable temperatures and added to soils with varying OM and clay contents.…”
Section: Introductionmentioning
confidence: 97%